An Approach to Automatic Building Information Modeling-Based Generation of Finite Element Models of Different Complexity and Finite Element Dimensionality - Iryna Rudenko; Yuri Petryna (Buildings)
(1) The presented paper proposes an approach to the BIM-based generation of FE models of different complexity and FE dimensionality. This is particularly important as different FE models are needed to assess various structural or material limit states for the same structure, affecting the accuracy and efficiency of simulations. (2) The basis of the BIM model is an IFC file that is enriched with FEM- and, if desired, SHM-relevant information. The geometry of the objects is described by SweptSolid representation with a parameterized profile definition. Moreover, material properties, supports, and structural connections are specified within the BIM model. Afterwards, the data are extracted from the IFC file. Additionally, the geometry of the structure is modified depending on the desired FE dimensionality. Subsequently, ANSYS MAPDL commands are generated and written to the macro file. (3) The approach is illustrated by an example of a laboratory test structure. Four FE models of different complexity and FE dimensionality are successfully generated based on the IFC file and used for numerical simulations. (4) This study demonstrates the efficiency, practicality, and functionality of the proposed approach, offering a robust solution for generating FE models that can be used across multiple structural analysis scenarios.